Microbial Diversity in Bulk and Rhizosphere Soil of Ranunculus glacialis Along a High-Alpine Altitudinal Gradient - Praeg, Nadine; Pauli, Harald; Illmer, Paul (Frontiers in Microbiology, 2019)
Serving as ‘natural laboratories’, altitudinal gradients can be used to study changes in the distribution of microorganisms in response to changing environmental conditions that typically occur over short geographical distances. Besides, rhizosphere zones of plants are known to be hot-spots for microbial diversity and to contain different microbial communities when compared with surrounding bulk soil. To discriminate the effects of altitude and plants, we investigated the microbial communities in the rhizosphere of Ranunculus glacialis and bulk soil along a high-alpine altitudinal gradient (2600–3400 m a.s.l.). The research area of this study was Mount (Mt.) ‘Schrankogel’ in the Central Alps of Tyrol (Austria). Our results point to significantly different microbial diversities and community compositions in the different altitudinal belts. In the case of prokaryotes, environmental parameters could explain 41% of the total variation of soil communities, with pH and temperature being the strongest influencing factors. Comparing the effects derived from fraction (bulk vs. rhizosphere soil) and environmental factors, the effects of the roots of R. glacialis accounted for about one third of the explained variation. Fungal communities on the other hand were nearly exclusively influenced by environmental parameters accounting for 37.4% of the total variation. Both, for altitudinal zones as well as for bulk and rhizosphere fractions a couple of very specific biomarker taxa could be identified. Generally, the patterns of abundance of several taxa did not follow a steady increased or decreased trend along the altitudinal gradient but in many cases a maximal or minimal occurrence was established at mid-altitudes (3000–3100 m). This mid-altitudinal zone is a transition zone (the so-called alpine-nival ecotone) between the (lower) alpine grassland/tundra zone and the (upper) sparsely vegetated nival zone and was shown to correspond with the summer snow line. Climate change and the associated increase in temperature will shift this transition zone and thus, might also shift the described microbial patterns and biomarkers.